Students attitude towards science, technology, engineering and mathematics in developing career aspiration - Razali, Fazilah; Talib, Othman; Abdul Manaf, Umi Kalthom; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2018)
Integrating Science, Technology, Engineering and Mathematics (STEM) will benefit the national economy. Therefore, educators and school community have given appropriate attention to students that are competitive to fulfill the industrial economy needs. This research studied the nurturing of attitude towards STEM among students in developing interest in STEM careers by using the survey method. Research objective to determine direct influence between attitude towards STEM and development of STEM career interest among Form Four science stream students. A total of 398 Form 4 students from the science stream in secondary school in Selangor, Malaysia have been chosen as respondents. The Student Attitudes questionnaire toward Science, Technology, Engineering, and Math (S-STEM) and interest in STEM career is used to study the influence of attitude towards STEM in developing STEM career aspiration among science stream students. Result of the study shows that the students attitude in developing STEM career recorded the value p =.002 and is significant with the value of p < 0.05. Besides, the effect of influence for the three attitude sub-constructs towards STEM which are science (0.65), technology & engineering (0.65) and mathematics (0.59) recorded the value of more than 0.3 which give a huge impact of research. Thus, the nurturing of attitude towards STEM among students provide a new dimension in the learning process for future need compared to considering it as a study requirement only for academic purpose.